The Effect of Foreign Direct Investment (FDI), Zakat Distribution and Government Spending on Economic Growth with Human Development Index as Moderating Variable - Itsnaini, Nurul Kholifah Aminatul; Bawono, Anton (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This study aims to determine the effect of foreign direct investment, zakat distribution and government spending on economic growth in Indonesia in 2019-2024 with the Human Development Index as a moderating variable. This type of research is quantitative with a population of all provinces in Indonesia. Determination of the Saturated Sampling sample with criteria determined by the researcher so that a sample of 33 provinces was obtained during the observation period (2019-2024). The type of data used is panel data. Using the analysis method used includes descriptive test, stationary test, multiple liner regression test, T test, F test, R2 test, classical assumption test and MRA test. In the Moderated Regression Analysis (MRA) test using Eviews 13 data processing software, the results showed that the government expenditure variable had no effect on economic growth. Based on the MRA test, HDI is able to moderate government spending on economic growth and HDI is not able to moderate the distribution of Zakat on economic growth.